2005
DOI: 10.1074/jbc.m506412200
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Core Protein Inhibits Mitochondrial Electron Transport and Increases Reactive Oxygen Species (ROS) Production

Abstract: Hepatitis C infection causes a state of chronic oxidative stress, which may contribute to fibrosis and carcinogenesis in the liver. Previous studies have shown that expression of the HCV core protein in hepatoma cells depolarized mitochondria and increased reactive oxygen species (ROS) production, but the mechanisms of these effects are unknown. In this study we examined the properties of liver mitochondria from transgenic mice expressing HCV core protein, and from normal liver mitochondria incubated with reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
363
0
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 380 publications
(387 citation statements)
references
References 60 publications
(45 reference statements)
16
363
0
8
Order By: Relevance
“…This would not be unexpected because the core protein itself has been implicated as a major cause of HCV-induced oxidative stress. 26,49,50 In conclusion, this study has identified FOXO3 as a novel protective factor for alcoholic liver injury. Loss of FOXO3 expression in mice results in a phenotype in which alcohol consumption causes severe liver injury that is histologically similar to human alcoholic hepatitis.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…This would not be unexpected because the core protein itself has been implicated as a major cause of HCV-induced oxidative stress. 26,49,50 In conclusion, this study has identified FOXO3 as a novel protective factor for alcoholic liver injury. Loss of FOXO3 expression in mice results in a phenotype in which alcohol consumption causes severe liver injury that is histologically similar to human alcoholic hepatitis.…”
Section: Discussionmentioning
confidence: 60%
“…HCV transgenic mice (SL-139 line) were generated on a C57BL/6J background, as previously described. 26 These mice are a hemizygous model and express HCV structural proteins (core, E1, E2, and p7) in hepatocytes under control of the murine albumin enhancer/promoter. Sod2 þ/À mice on a C57BL/6J background have been previously described.…”
Section: Mouse Strains and Alcohol Feedingmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondria were purified using Nycodenz (Nycomed Pharma, Zürich, Switzerland) according to the protocols reported by Okado-Matsumoto et al 17 For transient transfection experiments, HepG2 cells were transfected with a core-expression plasmid using TransIT-LT1 (Mirus Bio, Madison, WI). Huh7 cells harboring HCV genotype 1b full-genomic (RCYM1) 18 or subgenomic replicon (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), and livers of 3-month-old core-gene transgenic mice 2 were also used for the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In livers of transgenic mice harboring the core gene, increased ROS production has been observed. [7][8][9] A recent study found, by the proteomic profiling of biopsy specimens, that an impairment in key mitochondrial processes, including fatty acid oxidation and oxidative phosphorylation, and in the response to oxidative stress occurs in HCV-infected human liver with advanced fibrosis. 10 Therefore, it is probable that the HCV core protein affects mitochondrial functions because such pathogenesis is observed in both HCV core-transgenic mice and HCV-infected patients.…”
mentioning
confidence: 99%